2020
DOI: 10.1155/2020/8834331
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Study on the Reinforcement of Silt with Permeable Polyurethane by Penetration Grouting

Abstract: To meet the demand of antiseepage and reinforcement of soil dams, a kind of permeable polyurethane grouting material was developed. A visual steady-pressure grouting test device was designed to study the law of polyurethane diffusion and reinforcement in silt under different pressure, and the interaction mechanism of grout and soil body structure was explored microscopically. The results showed that, with the increase in the grouting pressure, the diffusion speed rose, and the diffusion pattern of grout in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Several studies [32][33][34][35][36][37] have investigated different aspects of PU such as, its durability, tensile properties, mechanical properties, and toxicity.…”
Section: Short Background On Chemical Groutingmentioning
confidence: 99%
“…Several studies [32][33][34][35][36][37] have investigated different aspects of PU such as, its durability, tensile properties, mechanical properties, and toxicity.…”
Section: Short Background On Chemical Groutingmentioning
confidence: 99%
“…At present, grouting materials mainly include cement, cement-water glass, clay–cement, chemical grouting materials and resins, etc. [ 6 , 7 , 8 , 9 ]. Among them, clay–cement grouting materials have good application value due to their low cost, good stability and strong anti-permeability [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [12] conducted field test research on the diffusion characteristics of expansive polymer materials in soil and found that the polymer developed flaky fracture diffusion in soil and finally formed a wedge-shaped section in the cracks. Wang et al [13] studied the diffusion and reinforcement law of polymers in silt under different pressures and found that polymers can effectively reduce the porosity of soil to improve the properties of soil. Valentino et al [14] studied the mechanical properties of two different types of polyurethane through experiments and found that the higher the restraint stress in the expansion stage of polyurethane, the higher the density after hardening.…”
Section: Introductionmentioning
confidence: 99%